2015
DOI: 10.18632/oncotarget.5549
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive investigation of oncogenic driver mutations in Chinese non-small cell lung cancer patients

Abstract: PurposeTo determine the frequency of driver mutations in Chinese non-small cell lung cancer (NSCLC) patients.MethodsComprehensive mutational analysis was performed in 1356 lung adenocarcinoma, 503 squamous cell carcinoma, 57 adenosquamous lung carcinoma, 19 large cell carcinoma and 8 sarcomatoid carcinoma. The effect of EGFR tyrosine kinase inhibitors (TKIs) on EGFR-mutated lung adenocarcinoma patients after disease recurrence was investigated.ResultsMutations in EGFR kinase domain, HER2 kinase domain, KRAS, B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
68
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(77 citation statements)
references
References 21 publications
8
68
1
Order By: Relevance
“…EGFR mutations can also be detected in nonadenocarcinoma. Specifically, several previous reports have shown that EGFR mutations can be detected in 35.1–44.0%, 3.9–10.0%, and 11.5–14.3% of patients with adenosquamous carcinoma, squamous cell carcinoma and large cell carcinoma, respectively232425. The results of our prospective multicenter study (IGNITE study) demonstrated that in an Asian population with lung squamous cell carcinoma, the EGFR mutation frequency was 10%26.…”
Section: Discussionsupporting
confidence: 53%
“…EGFR mutations can also be detected in nonadenocarcinoma. Specifically, several previous reports have shown that EGFR mutations can be detected in 35.1–44.0%, 3.9–10.0%, and 11.5–14.3% of patients with adenosquamous carcinoma, squamous cell carcinoma and large cell carcinoma, respectively232425. The results of our prospective multicenter study (IGNITE study) demonstrated that in an Asian population with lung squamous cell carcinoma, the EGFR mutation frequency was 10%26.…”
Section: Discussionsupporting
confidence: 53%
“…EGFR mutation testing was established as an essential part of standard care for adenocarcinoma of the lung but not for non-adenocarcinoma. In recent years, several prospective and retrospective studies have demonstrated that epidermal growth factor receptor mutations can be detected in 35.1-44.0, 3.9-10.0, and 11.5-14.3 % of ASC, SCC, and LCLC, respectively (Wang et al 2015;Kang et al 2007;Zhang et al 2015a, b, c;Rosell et al 2009;Han et al 2015), frequencies that were much higher than expected. A retrospective study demonstrated that EGFR TKIs showed efficacy in EGFR-mutated non-adenocarcinoma patients, but not in EGFR wild-type patients (Fang et al 2013).…”
Section: Discussionmentioning
confidence: 91%
“…SCC and LCLC patients probably have a minor adenocarcinomatous component that was undetected due to the limitation of the small diagnostic biopsy. This may also explain the relatively higher frequency of EGFR mutations in the ASC population compared with the SCC and LCLC patients (Wang et al 2015;Kang et al 2007;Zhang et al 2015a, b, c;Rosell et al 2009;Han et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…These sensitive mutations are found in approximately 10% of Western patients and 63.1% of Chinese patients with NSCLC [57]. Several randomized controlled trials that enrolled patients harbouring EGFR-activating mutations demonstrated that EGFR-TKI is superior to chemotherapy in terms of progression-free survival (PFS) and objective response rate (ORR) [811].…”
Section: Introductionmentioning
confidence: 99%